The Impact of Sovereign Wealth Fund Acquisitions on Corporate Performance and Value. A Comparative Study in the Madrid and Saudi Stock Exchanges - SAADON, Basim Khaleel Saadon; LLANO PAZ, Fernando de; MARTÍNEZ FERNÁNDEZ, Paulino (Theoretical and Practical Research in Economic Fields; Vol 16 No 2 (2025): TPREF, Volume XVI, Issue 2(34), Summer 2025DO - 10.14505/tpref.v16.2(34).19, 2025)
This study investigates the influence of sovereign wealth fund (SWF) investments on the financial performance of firms in Saudi Arabia and Spain. Findings indicate that SWF investments exert a notable influence on average share prices, accounting for a considerable portion of the variation in stock values across both countries. Conversely, no significant relationship was found between SWF investments and other financial indicators such as return on investment, liquidity ratio, financial leverage, and profitability ratio. The analysis underscores the relevance of a firm’s national context when assessing the implications of SWF activity, as such investments may alter ownership structures and strategic directions. Additionally, the study emphasizes that SWF decisions are closely linked to broader economic and political developments, necessitating continuous monitoring and contextual evaluation. To explore these dynamics, the research utilized statistical tools such as regression models and coefficients of determination, enabling a clear measurement of the investments’ effects on financial indicators. The study concludes with several recommendations: further investigation into other variables influencing financial performance, stronger collaboration with SWFs as part of strategic investment planning, and improved transparency through consistent financial disclosure. Moreover, longitudinal and cross-sectoral comparative research is encouraged to deepen the understanding of SWF impacts globally.